Monetary Policy Coordination and the Role of Central Banks - Mohan, Rakesh (IMF Working Papers; Working Paper, 2014)
The unconventional monetary policies (UMPs) pursued by the advanced economies (AEs) have posed macroeconomic challenges for the emerging market economies (EMEs) through volatile capital flows and exchange rates. AE central banks need to acknowledge and appreciate the spillovers resulting from such UMPs. Central banks of the AEs, who have set up standing mutual swap facilities, should explore similar arrangements with other significant EMEs with appropriate risk mitigation measures. These initiatives could do much to actually curb volatility in global financial markets and hence in capital flows to EMEs, thus obviating the need for defensive policy actions on the part of EMEs.